An Interactive Tool to Model Virtual Abdominal and Cerebral Aneurysms - Silva, Rodrigo L. S.; Camargo, Eduardo; Blanco, Pablo Javier; Pivello, Márcio; Feijóo, Rául A. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2008: Anais do VIII Workshop de Informática Médica, 2008)
This paper presents a modeling tool to create hemodynamic pathologies, based on geometrical singularities, such as Aneurysms and Stenoses. An interactive tool that allows the positioning of virtual aneurysms will be explained and some simulation results will be presented. These pathologies can be added based on parameterized geometries or over real arterial geometries, usually obtained via segmentation techniques from medical images. This tool allows modeling cerebral and abdmonimal aneurysms and stenoses interactively.